Int J Dermatol Skin Care 2021
DOI: 10.36811/ijdsc.2021.110006
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary approach to the comprehensive treatment of edentulous patients with perioral wrinkles of the skin

Abstract: Objectives: The purpose of this study was to comparative analysis of effectiveness of isolated use of intradermal injections of modified hyaluronic acid (Hyalorepair 04) and its combination with platelet-rich autologous plasma in edentulous patients with perioral wrinkles of the skin. Materials and Methods: A total of 56 patient’s presence of perioral wrinkles of the skin participate in the study after dental implant prosthodontics rehabilitations. They were randomly divided into 2 groups in accordance with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The intervention group experienced significant improvements in the severity of facial wrinkles and skin hydration level compared to the control group. Other studies, including those published by Hegde [67], Cervino et al [68], van Loghem et al [69], and Hakobyan et al [70], also supported the use of HA injections in edentulous patients, emphasizing its safety and tolerability without any serious adverse events reported. The authors of these studies suggested that HA injections could serve as a safe and effective alternative or complementary treatment to traditional dental prostheses for enhancing oral and facial health in fully edentulous patients.…”
Section: Skin and Lip Rejuvenationmentioning
confidence: 81%
“…The intervention group experienced significant improvements in the severity of facial wrinkles and skin hydration level compared to the control group. Other studies, including those published by Hegde [67], Cervino et al [68], van Loghem et al [69], and Hakobyan et al [70], also supported the use of HA injections in edentulous patients, emphasizing its safety and tolerability without any serious adverse events reported. The authors of these studies suggested that HA injections could serve as a safe and effective alternative or complementary treatment to traditional dental prostheses for enhancing oral and facial health in fully edentulous patients.…”
Section: Skin and Lip Rejuvenationmentioning
confidence: 81%